Influencia de los factores psicosociales en el desempeño académico de etnias ecuatorianas: caso carreras de Administración de la ESPAM MFL - Alcívar Zambrano, Hernando Jair (2024)
The objective of this curricular integration work was to analyze the psychosocial factors to strengthen the academic performance of students of Ecuadorian ethnic groups in the Public Administration and Business Administration careers of the ESPAM MFL, during the period 2022-2023, for which The choice of university majors and their influence by psychosocial factors was addressed, which helped to understand how they can affect mental health and academic performance in the case study: Public Administration and Business Administration majors at ESPAM MFL. Also, inductive, deductive and analytical-synthetic methods were incorporated, in addition, interview and survey techniques were applied, organized for a comprehensive understanding of the respective process. With this, an interconnected network of psychosocial factors was identified such as stress that affects student performance. Additionally, it was established that the connection with cultural identity, academic self-efficacy, perception of discrimination, and efficient time management are critical elements. That influence emotional well-being, student motivation and academic performance. Therefore, it is summarized that it is necessary and important to apply improvement actions focused on psychosocial support, which adapt to the specific needs of the students of the analyzed careers, in order to strengthen academic and emotional well-being, optimizing the experience. Educational, social and cultural, with practical actions in institutional decision-making.